Struktur und Organisation des mentalen Lexikons in Kontext psychologischer Gedächtnistheorien - Legutko-Marszałek, Iwona (Glottodidactica, 2008)
The article presents the concept of mental lexicon's structure in context of memory theory. Mental lexicon has been defined as the part of long-term memory, where words of a particular language are gathered together with all the information concerning the structure of that particular language. Furthermore, the article points out the organization and connection between lexical units, as well as semantic relations between them. Examples depict the feasible process of activation of individual words in the mental lexicon.